Influence of different loads on the properties of lightweight composite - Kligys, Modestas; Sinica, Marijonas; Sezemanas, Georgijus; Miškinis, Kęstutis; Vaitkus, Saulius (Journal of Civil Engineering and Management, 2012)
The paper describes the study on the operational properties of lightweight composite with density of 150–350 kg/m3. It was established that these properties depend on the ratio of porous cement matrix and inclusions of crushed expanded polystyrene packing tare waste per unit volume of the lightweight composite. Studies have demonstrated that when the density of lightweight composite varies in the above mentioned limits, the compressibility amounts to 2.4–0.8 mm, point load – 0.38–3.39 kN, dynamic stiffness – 35–135 MN/m3, and reduction in normalised impact sound pressure level – 26–17 dB. The dependences between the established properties and the density of lightweight composite are showed in the equations of regression. Possible versions for the use of lightweight composite in different constructions of floors and roofs are also provided.